“Alternativas constructivas para la implementación de huertos orgánicos en viviendas ubicadas en las zonas urbanas.” - Olvera Torres, Johann José (2022)
Ecuador is a country full of rich ecosystems and biodiversity, so it is highly recommended and optimal to promote new urban and sustainable methodologies for people living in cities, in order to form a food sovereignty, which balance the food and nutrition of low-income families in these areas and also benefit economically from these activities. The document mentions constructive alternatives for the implementation of organic gardens in homes located in urban areas, emphasizing the importance of organic gardens as a means of independent sustenance by the communities, their benefits to a great extent in the growth of urban agriculture, within the cities and therefore a positive contribution to environmental sustainability, with the development of these gardens. The conclusions describe that the complementation of organic gardens within urban areas, contributes to the food supply of these areas, and those with economic problems, promoting the production of organic food and high nutritional quality, creating a sustainable system for families in these urban areas, contributing to their growth, The use and development of shared organic gardens contributes a lot to the cultural and social aspects, since in addition to promoting an adequate environmental education, it also helps to create relationships between the people involved in these gardens, the transmission of information helps to generate new ideas, which can develop new techniques and ingenious discoveries on the part of the communities.